Failure of random networks - Wansoo T. Rhee (International Journal of Mathematics and Mathematical Sciences)
This paper studies random failure of networks when we know the probability of failure of each link but we know nothing about the intercorrelation of these failures. Without any assumption on the structure of the network, we compute the probability that there still exists a path from the source to the sink after the worst possible failure of the network.